Household risk-sharing channels - Pierfederico Asdrubali; Simone Tedeschi; Luigi Ventura (Quantitative Economics, 2020)
This paper aims to fill the gaps in the analysis of risk-sharing channels at the microlevel, both within and across households. Using data from the Bank of Italy's Survey on Household Income and Wealth covering the financial crisis, we are able to quantify in a unified and consistent framework several risk-sharing mechanisms that so far have been documented separately. We find that Italian households were able to smooth on average about 85% of shocks to household head's earnings in both 2008-2010 and 2010-2012 spells. The most important smoothing mechanisms turn out to be self-insurance through savings/dissavings (40% and 47% in 2008-2010 and 2010-2012, respectively), and within-household risk-sharing (16% and 14%). Interestingly, risk-sharing through portfolio diversification and private transfers is rather limited, but the overall percentage of shock absorption occurring through private risk-sharing channels hovers around four-fifths, as opposed to around one-fifth of a shock cushioned by taxes and public transfers, excluding pensions. In addition, by exploiting subjective expectations on the following year's household income, we find significant evidence of a lower degree of smoothing of persistent shocks.
Keywords: C31; D12; E21; 330; Household risk-sharing; precautionary savings; consumptionsmoothing; income smoothing